THE IMPACT OF DEVELOPING AN OPEN DATA ECOSYSTEM IN PUBLIC FINANCE ON ECONOMIC EFFICIENCY - Javokhir Abdukhakimovich Aripov (Innovate Conferences, 2025)
In modern public governance systems, the effectiveness of state financial management is increasingly determined by the accessibility, reliability, and usability of information available to stakeholders. The development of an open data ecosystem in public finance has emerged as a critical institutional mechanism for enhancing transparency, strengthening accountability, and improving the quality of economic decision-making. Open financial data not only expands public oversight over government activities but also functions as an economic resource that contributes to efficient allocation of public funds, improved investment climate, and increased competitiveness within the national economy.